Normocephalic Pancraniosynostosis: A Report of a Surgical Technique. Issue 5 (July 2017) - Czerwinski, Marcin; Monsivais, Sharon
Abstract : Abstract: Normocephalic pancraniosynostosis is defined as the premature fusion of 3 or, more major sutures in the absence of another primary etiology, including primary, microcephaly, ventriculoperitoneal shunting, hypothyroidism, rickets, mucopolysaccharidoses, or other lysosomal storage diseases. It is very rare, thus far only 6 patients have been reported in the literature. Patients tend to present much later than those with single sutural, synostoses, and up to half have evidence of elevated intracranial pressure. The authors wish to present another patient, with emphasis on a unique treatment approach.